2015
DOI: 10.1007/s11664-015-4070-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Nanotubes on Thermoelectric Properties in Zn0.98Al0.02O

Abstract: Thermoelectric oxides can provide the advantage of high-temperature stability in oxygen-containing atmospheres. It is known that the incorporation of multiwalled carbon nanotubes (mw-CNT) can change the thermoelectric as well as the structural properties of oxides. Here, we report the influence of mw-CNT on the thermoelectric properties of Al-doped ZnO (AZO). The preparation of the mw-CNT-added AZO was done using an ultrasonic mixing of the starting materials followed by a spark plasma sintering process under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…[3][4][5] To achieve high conversion efficiency, the TE material must have a high power factor (S 2 σ), as well as low total thermal conductivity. [6][7][8] However, due to the intercorrelation of the transport parameters, optimizing the TE performance is relatively complex. Because the electrical properties involving S, σ and κ e are strongly coupled, [9] improving one of these three parameters will result in compensation for other parameters that impede progress toward improving TE performance.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] To achieve high conversion efficiency, the TE material must have a high power factor (S 2 σ), as well as low total thermal conductivity. [6][7][8] However, due to the intercorrelation of the transport parameters, optimizing the TE performance is relatively complex. Because the electrical properties involving S, σ and κ e are strongly coupled, [9] improving one of these three parameters will result in compensation for other parameters that impede progress toward improving TE performance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a good conductive network is established in the matrix owing to the homogeneous dispersion of in-situ grown CNTs, which facilitates the transport of electrons. In contrast, for the sample with commercial CNTs by ultrasonic technology, the electrical conductivity is much lower, mainly due to the agglomeration of CNTs, which prevents the excellent conductivity of CNTs from being effectively utilized [34].…”
Section: Resultsmentioning
confidence: 99%
“…They have been thus widely used as a reinforcement in many fields [31][32][33]. For example, Dreßler et al [34] mixed AZO powders and multi-walled CNTs by ultrasonic dispersion and mechanical milling, and then sintered the mixture by the spark plasma sintering (SPS). The results indicated that the thermal conductivity decreased from 31.2 to 26 W•m −1 •K −1 after the incorporation of multi-walled CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated that the energy barrier should be adjusted to 0.2 eV in order to obtain optimal energy filtering effect. [ 175 ] Some research found that increasing the CNT concentration increased electrical conductivity, [ 172,174,176,177 ] whereas others found the reverse. [ 178–181 ] The changing CNT content might explain this discrepancy.…”
Section: Discontinuous Interface Modificationmentioning
confidence: 99%